2012
DOI: 10.1088/1674-1056/21/1/013401
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reagent vibration on the stereodynamics of the Li + HF → LiF + H reaction

Abstract: We investigate the influence of reagent vibration on the stereodynamics of the title reaction by the quasi-classical trajectory on the Aguado-Paniagua2-potential energy surface developed by Aguado et al. (J. Chem. Phys. 1997 106 1013). The cross sections and reaction probability as functions of the reagent vibration are calculated in the centre-of-mass frame. The product angular distributions of p(θr), p(φr), and p(θr,φr), which reflect the vector correlation, are also presented and discussed. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Theoretical studies like the exact quantum probabilities for Li+HF and its isotopic variants have been reported by Laganà [12]. In 2012, Li et al have presented the reagent vibration effect for the reaction [13].…”
Section: Introductionmentioning
confidence: 97%
“…Theoretical studies like the exact quantum probabilities for Li+HF and its isotopic variants have been reported by Laganà [12]. In 2012, Li et al have presented the reagent vibration effect for the reaction [13].…”
Section: Introductionmentioning
confidence: 97%
“…[11] Recently, the stereodynamical code developed by Han et al [7][8][9][10] has been renewed and used successfully in many chemical reactions. [12][13][14][15][16][17] In the present work, we use this computational code to explore the product rotational polarization in the title reaction.…”
Section: Introductionmentioning
confidence: 99%
“…By using the QCT method, Li et al investigated the vibrational effect on the Li+HF reaction. [31] Later, Yue et al studied the isotopic effect where the product polarization showed decreasing trends with the increase of the mass. [32] As we know, the reverse reaction is also important for obtaining the reaction mechanism.…”
mentioning
confidence: 99%